What drives soil degradation after gravel mulching for 6 years in northwest China? - Qiu, Yang; Chen, Xingyi; Wang, Yajun; Zhang, Yubao; Xie, Zhongkui (Frontiers in Microbiology, 2023)
Gravel mulch is an agricultural water conservation practice that has been widely used in the semi-arid region of northwest China, but its effectiveness is now lessening due to soil degradation caused by long-term gravel mulching. In this study, we report on a 6-year-long gravel mulch experiment conducted in the northwestern Loess Plateau to evaluate the impact of gravel mulch on soil physicochemical properties and microbial communities, with the objective of clarifying the causes of long-term gravel mulching-induced land degradation. After 6 years mulching, we found that gravel mulched soil contained significantly higher concentrations of total carbon and total organic carbon than non-mulched soil (control). Long-term gravel mulching significantly changed the soil microbial diversity and abundance distribution of bacterial and fungal communities. Notably, the relative abundance of Acidobacteria was significantly higher under gravel mulching than the control (no mulching), being significantly greater in the AG treatment (small-sized gravel, 2–5 mm) than all other treatments. Conversely, the relative abundance of Actinobacteria was significantly lower under gravel mulching than the control, being the lowest in the BG treatment (large-sized gravel, 40–60 mm). At the same time, the relative abundance of Bacteroidetes was significantly lower in AG yet higher in BG vis-à-vis the other treatments. Of the various factors examined, on a 6-year scale, the capture of dust by gravel mulch and altered carbon and nitrogen components in soil play major contributing roles in the compositional change of soil microorganisms. These results suggest that modified soil material input from gravel mulching may be the key factor leading to soil degradation. More long-term experimental studies at different sites are now needed to elucidate the mechanisms responsible for soil degradation under gravel mulching.